2013
DOI: 10.1186/1746-1596-8-208
|View full text |Cite
|
Sign up to set email alerts
|

Association of microRNA-126 expression with clinicopathological features and the risk of biochemical recurrence in prostate cancer patients undergoing radical prostatectomy

Abstract: ObjectiveNumerous studies have suggested that microRNA-126 (miR-126) is involved in development of various cancer types as well as in malignant proliferation and invasion. However, its role in human prostate cancer (PCa) is still unclear. The aim of this study was to investigate miR-126 expression in PCa and its prognostic value for PCa patients undergoing radical prostatectomy.MethodsA series of 128 cases with PCa were evaluated for the expression levels of miR-126 by quantitative reverse-transcription PCR (q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Furthermore, expression of miR-126 was found to be increased in metastatic colorectal cancer patients responding to the first-line treatment with capecitabine and oxaliplatin, compared to the patients showing to response [55]. In prostate cancer, miR-126 was reported to be downregulated and its expression level was associated with tumor advance stage and positive lymph node [56].…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, expression of miR-126 was found to be increased in metastatic colorectal cancer patients responding to the first-line treatment with capecitabine and oxaliplatin, compared to the patients showing to response [55]. In prostate cancer, miR-126 was reported to be downregulated and its expression level was associated with tumor advance stage and positive lymph node [56].…”
Section: Discussionmentioning
confidence: 95%
“…It has been demonstrated that miRNAs can enter into systemic circulation via certain mechanisms, including exosome secretion, cell death and blebbing, and that these circulating miRNAs could be used as potential markers for and in the follow-up of certain diseases (24). So far, studies have focused on the changes of miRNA expression levels associated with cancer (1,61). However, to the best of our knowledge there are no studies that have investigated the effects of radiation on platelet miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer was a common global malignancy among men in 2012 (1,2). Ionizing radiation is used to treat various types of cancer (3), including localized prostate cancer (4).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of miR-126 has been observed in many cancers, such as breast cancer (8), lung cancer (10) and prostate cancer (17). The decreased expression of miR-126 was associated with poor metastasis-free survival of breast cancer patients (18).…”
Section: Discussionmentioning
confidence: 99%